Development of Nutmeg Sweets Making Business in Gampong Hilir, Tapaktuan District 1978 – 2021 - Oppy Chotsria Dayanti (Riwayat: Educational Journal of History and Humanities, 2022)
The study, entitled "Business Development of Candied Nutmeg Making UD. Dianti Gampong Hilir Kecamatan Tapaktuan 1978 - 2021 "This aims to determine the initial process of the birth of the business of making candied nutmeg of UD. Dianti Gampong Hilir, Tapaktuan District from 1978-2021 and to find out how the development of the business of making candied nutmeg UD. Dianti Gampong Hilir, Tapaktuan District from 1978 - 2021. This study uses a qualitative approach to the type of historical research. The subjects in this study were the owners of candied nutmeg. Data collection techniques using observation and interview techniques. All data from observations and interviews were processed with the data analysis stage, namely, data reduction, data presentation, and verification / drawing conclusions. The results of this study can be concluded that the development of the business of making candied nutmeg UD. Dianti Gampong Hilir, Tapaktuan District is quite good. Among them, the owner of candied nutmeg is getting more advanced than usually selling only candied nutmegs but now there are new products produced by the owner of candied nutmeg due to business development from year to year.